2021
DOI: 10.5937/straman2103072s
|View full text |Cite
|
Sign up to set email alerts
|

Does capital structure affect the differences in the financial performance of small enterprises?

Abstract: Capital structure refers to the combination of debt and equity that the company uses to finance overall operations and growth. One of the most common problems of small enterprises is difficult access to various sources of financing, which is certainly reflected in their capital structure. Deciding on capital structure is one of the most important activities in the company, given that it significantly determines the performance of the company, but also the competitiveness and sustainability of the business. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…The average total leverage of the analyzed companies is 0.56, varying widely from 0.03 to 4.63. The average value of total leverage is comparable to the leverage values obtained in other studies conducted in developing countries, where it is significant to point out that high values of total leverage are due to very high levels of short-term leverage, while on the other hand, these companies have a very low level of long-term leverage [53,72]. Since the sample consisted of companies that were in operation for all years of the observed period, the above also influenced the average age of the analyzed companies to be relatively high.…”
Section: Data Analysis Results and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The average total leverage of the analyzed companies is 0.56, varying widely from 0.03 to 4.63. The average value of total leverage is comparable to the leverage values obtained in other studies conducted in developing countries, where it is significant to point out that high values of total leverage are due to very high levels of short-term leverage, while on the other hand, these companies have a very low level of long-term leverage [53,72]. Since the sample consisted of companies that were in operation for all years of the observed period, the above also influenced the average age of the analyzed companies to be relatively high.…”
Section: Data Analysis Results and Discussionsupporting
confidence: 81%
“…One of the limitations of this research refers to the use of total leverage as a proxy for capital structure. Companies in developing countries have a very high degree of participation of short-term financing sources in the capital structure [53,72]. Not all forms of debt are equally likely to curtail overinvestment.…”
Section: Data Analysis Results and Discussionmentioning
confidence: 99%
“…By and large, empirical studies indicate that financing, capital structure, especially long-term and total debt ratios, negatively affect the performance of small and medium enterprises (SMEs) (Harash et al, n.d.) However, the relationship between capital structure and financial performance can vary depending on the country and the type of debt (Stephen Wagana & of Nairobi, 2014). Financial capital also can enable MSMEs to engage in financial investments, which can help them grow (Stoiljković et al, 2021).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…According to findings, a certain level of liquidity is negatively related to the debt and financial performances (Zainudin, 2019). In addition, the impact of leverage on the financial performance of companies in the Autonomous Province of Vojvodina, Republic of Serbia, showed that the level of leverage does not have a significant impact on the financial performance of the company and that the most significant results were indicated in the net profit margin, which shows the decrease in net profit margin when leverage is higher (Stoiljković, Tomić & Uzelac 2021).…”
Section: Theoretical Background Of Reitsmentioning
confidence: 98%